PENERAPAN MODEL TEAM GAMES TOURNAMENT (TGT) DENGAN MEDIA VISUAL DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SDN 1 JATISARI TAHUN AJARAN 2014/ 2015 - Widyanti, Iin (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The application of Team Games Tournament (TGT) model using visual media in improving the teaching learning process of Social Science for the fifth grade students of SDN 1 Jatisari in the academic year of 2014/2015. The objectives of this study to improve the teaching learning process of sosial science for the fifth grade students through Team Games Tournament (TGT) model using visual media. This study is categorized as a collaborative classroom action research conducted within three cycles consisting the following steps planning, implementation, observation and reflection. The subject of the study were 26 fifth grade students of SDN 1 Jatisari. The data collection techniques were tests, observation, interviews and documentation. The result of the study show that the application of Team Games Tournament (TGT) model using visual media improved the teaching learning process of social science for the fifth grade students of SDN 1 Jatisari in the academic year of 2014/2015.Keywords: Team Games Tournament, visual media, social science Abstrak: Penerapan Model Team Games Tournament dengan Media Visual dalam Peningkatan Pembelajaran IPS pada Siswa Kelas V SDN 1 Jatisari Tahun Ajaran 2014/2015. Penelitian ini bertujuan untuk meningkatkan pembelajaran IPS siswa kelas V SD  dengan menerapkan model Team Games Tournament dengan media benda visual. Penelitian ini merupakan penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus terdiri dari tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitiannya adalah siswa kelas V SDN 1 Jatisari yang berjumlah 26 siswa. Teknik pengumpulan data dalam penelitian ini menggunakan tes, observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan penerapan model Team Games Tournament dengan media visual meningkatkan pembelajaran IPS siswa kelas V SDN 1 Jatisari tahun ajaran 2014/2015Kata kunci: Team Games Tournament, Media Visual, IPS